Indicadores de sustentabilidade na pecuária leiteira em uma bacia hidrográfica - Almeida, Danilo Costa de (2018)
The determination of the level of the agroecological transition in rural properties is essential for directing actions of planning and execution of technical assistance and extension and for proposals of public policies that promote improvements in the quality of life of the rural population. Here, this evaluation was made using socioeconomic and environmental indicators with the MESMIS methodology, which was later submitted to geospatial analysis, with the basin as sample unit, where the rural community of Pedra Preta is inserted, and has 2 conservation units in its limits, these elements integrate the structural and methodological body of this study. The producers interviewed are classified as family farmers and reside on the property, where they have their main source of income in the dairy farming sector. Field research occurred from November 2016 to February 2017 with the application of questionnaires to 26 farmers who provided information for the evaluation of the agroecological transition index that was later spatialized in the QGIS software. Taking into account three dimensions: environmental, social and economic, we applied 25 indicators, where the transition rate calculated for the community was 67.8%. The main weaknesses were; lack of effluent treatment; ignorance of agroecology; and lack of environmental education. The properties with lower rates of agroecological transition are concentrated in the denser regions. The relief and the hydrography were related to the position of the headquarters, the rural producers are concentrated in the bedside area and at the mouth of the Pedra Preta river.